Development of an Android-based virtual laboratory as a database learning media for vocational school - Umami, Riza; Leksono, Ibut Priono; Rohman, Ujang (Jurnal Inovasi dan Teknologi Pembelajaran, 2023)
Abstract: Tujuan pengembangan dan penelitian ini adalah menghasilkan produk laboratorium virtual berbasis android sebagai media pembelajaran basis data kelas XI SMK dilengkapi buku petunjuk penggunaan “Vlab base” dan meningkatkan pemahaman serta hasil belajar siswa pada topik pengelolaan tabel pada basis data menggunakan Bahasa SQL. Prosedur pengembangannyamenggunakan  metode Research and Development (R&D) dan pendekatan pengembangan aplikasi model waterfall. Hasil validasi dari ahli media mencapai prosentase 92 (sangat layak), ahli desain 93 (sangat layak), dan ahli materi 94 (sangat layak). Uji kepraktisan mencapai prosentase 95 (sangat layak), kelompok kecil 90,67 (sangat layak), dan uji coba kelompok besar 93 (sangat layak) yang mempermudah siswa belajar dan praktikum mandiri memahami pengelolaan database berkategori sangat layak dan dapat digunakan guru dalam pembelajaran. Hasil pre dan post test siswa meningkatkan nilai hasil belajar siswa sebesar 100% berdasarkan kriteria efektivitas ketika digunakan dalam pembelajaran. Abstract: The goal of this research and development is to create an Android-based virtual laboratory product as a database learning medium for class XI Vocational School equipped with a manual for using "Vlab base" and to improve understanding and results of student learning in the topic of managing tables in databases using SQL language. The development procedure employed the research and development (R&D) method to create Android-based learning materials and the waterfall model application development approach. The validation results are 92% (very feasible) from the media experts, 93% (very decent) from the design experts, and 94% (very decent) from the material experts. The practicality test reaches 95% (very feasible), the small group reaches 90.67% (very feasible), and the large group trial obtains 93% (very feasible), making individual practice and learning simpler for pupils to understand database management that is categorized as very feasible and can be used by teachers in learning. Based on the criteria of effectiveness for learning, the results of the students' pre-test and post-test showed a 100% improvement in the value of student learning outcomes.